The Impact of Workload on Employee Performance at PT. Arista Auto Prima Pekanbaru - Arif, Harsa (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to analyze the influence of workload on employee performance at PT. Arista Auto Prima Pekanbaru, an automotive dealership company in Indonesia. The study examines both quantitative and qualitative workload dimensions and their correlation with various aspects of employee performance. Materials and methods: This quantitative study involved 87 employees from PT. Arista Auto Prima Pekanbaru, selected through proportionate random sampling. Data collection utilized validated questionnaires measuring workload dimensions and performance metrics. The research employed a correlational design with survey methodology. Structural Equation Modeling (SEM) analysis was conducted using SPSS version 26.0. Results: Statistical analysis revealed significant negative correlation between excessive workload and employee performance (r = -0.642, p < 0.01). Time pressure demonstrated the strongest negative impact on work quality (β = -0.573, p < 0.001). However, moderate levels of workload showed optimal performance outcomes, supporting an inverted U-shaped relationship. Department-specific analysis indicated varying workload threshold tolerances across operational units. Conclusions: The findings confirm that excessive workload adversely affects employee performance at PT. Arista Auto Prima Pekanbaru, while appropriate workload distribution enhances productivity. Implementation of workload balancing strategies, clear job descriptions, and supportive organizational culture are recommended for optimal employee performance and organizational success